2018
DOI: 10.3389/fimmu.2018.02455
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation of Physiology, Innate Immunity and Antibody Response to H1N1 Influenza Virus Infection During Pregnancy

Abstract: In 2009, the H1N1 swine flu pandemic highlighted the vulnerability of pregnant women to influenza viral infection. Pregnant women infected with influenza A virus were at increased risk of hospitalization and severe acute respiratory distress syndrome (ARDS), which is associated with high mortality, while their newborns had an increased risk of pre-term birth or low birth weight. Pregnant women have a unique immunological profile modulated by the sex hormones required to maintain pregnancy, namely progesterone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 161 publications
(193 reference statements)
1
45
0
Order By: Relevance
“…Estrogen plays an important role in the generation of classswitched and mutated antibodies and autoantibodies, thereby contributing to the greater response to microbial vaccines as well as the greater incidence of antibody-mediated autoimmunity, such as in systemic lupus erythematosus, in females (4,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)28). Indeed, we have shown that estrogen enhances AID expression by activating the HOXC4/HoxC4 promoter and inducing HoxC4, which is a critical Aicda promoter activator together with NF-κB (27,28).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Estrogen plays an important role in the generation of classswitched and mutated antibodies and autoantibodies, thereby contributing to the greater response to microbial vaccines as well as the greater incidence of antibody-mediated autoimmunity, such as in systemic lupus erythematosus, in females (4,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)28). Indeed, we have shown that estrogen enhances AID expression by activating the HOXC4/HoxC4 promoter and inducing HoxC4, which is a critical Aicda promoter activator together with NF-κB (27,28).…”
Section: Discussionmentioning
confidence: 90%
“…Estrogen plays an important role in boosting the production of mature antibodies and autoantibodies (1,2). This provides an explanation for the greater antibody response to microbial vaccines and infections as well as the greater incidence of antibody-mediated autoimmunity, such as systemic lupus erythematosus, in females (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Like protective antibodies against pathogenic microorganisms, pathogenic autoantibodies in humans and mice with systemic autoimmunity are generally class-switched and hypermutated, strongly suggest a role for estrogen in modulation of immunoglobulin (Ig) class switch DNA recombination (CSR) and somatic hypermutation (SHM).…”
Section: Introductionmentioning
confidence: 99%
“…Successful pregnancies require expression of PIBF, which promotes Th2 cytokine production and inhibition of NK cell activity, resulting in reduced cytolytic activity at the fetal-maternal interface and potentially increases maternal susceptibility to infection (25). This progesterone-responsive immunomodulatory protein has multiple splice variants.…”
Section: Pregnancy Increases Lung Viral Titers and Pathology In Influmentioning
confidence: 99%
“…However, this balance can be disrupted by viral pathogens that cross placental barrier. For example, Littauer and colleagues demonstrated that influenza virus infection disrupts progesterone production and upregulates inflammatory mediators such as cyclooxygenase-2 and prostaglandins, resulting in preterm birth and miscarriages [147]. Furthermore, using an animal model, the same group reported that viral load was negatively associated with progesterone concentration, and reduced progesterone expression was correlated with preterm birth in influenza virus-infected pregnant mice [148].…”
Section: Current Progress and Future Perspectives Of Studying Maternamentioning
confidence: 99%